DINAMIKA KEILMUAN HADIS DALAM PERSPEKTIF AHLI SUNAH DAN SYIAH IMAMIYAH - Alkadri Alkadri (Borneo : Journal of Islamic Studies, 2022)
This paper discusses the dynamics of hadith scholarship between Sunnaists and Shia Imamiyah, developing along with criticism and scholarly dialogue on hadith between these two groups so that it is necessary to conduct studies with a focus on the history of scientific formation, characteristics, advantages and disadvantages of each. The discussion method is in the form of literature review. Data analysis uses content analysis with a historical approach. Primary data is in the form of hadith science books and secondary data from hadith books and others according to the needs of the discussion. The findings of the discussion: Scholars of hadith Expert Sunnah was born from oral culture into writings that are collected in the books of hadith. It is inclusive, oriented towards rawi and matan criticism with the levels of valid, hasan, dha'if and maudhu' so that scientific dialogue is well systemized even though the determination of the authenticity of hadith cannot be separated from the subjectivity of hadith critics. Imamiyya Shia hadith scholarship is under the authority of the imam and is exclusive with the levels of sahih, hasan, muwastaq and dha'if so that scientific dialogue is based on the authority of the imam and the scientific system adopts sunnah experts.